Functional Magnetic Resonance Imaging of Working Memory and Executive Dysfunction in Systemic Lupus Erythematosus and Antiphospholipid Antibody–Positive Patients - Kozora, E.; Uluğ, A. M.; Erkan, D.; Vo, A.; Filley, C. M.; Ramon, G.; Burleson, A.; Zimmerman, R.; Lockshin, M. D. (Arthritis care & research (2010), 2016)
Objective Standardized cognitive tests and functional magnetic resonance imaging (fMRI) studies of systemic lupus erythematosus (SLE) patients demonstrate deficits in working memory and executive function. These neurobehavioral abnormalities are not well studied in antiphospholipid syndrome, which may occur independently of or together with SLE. This study compares an fMRI paradigm involving motor skills, working memory, and executive function in SLE patients without antiphospholipid antibody (aPL) (the SLE group), aPL‐positive non‐SLE patients (the aPL‐positive group), and controls. Methods Brain MRI, fMRI, and standardized cognitive assessment results were obtained from 20 SLE, 20 aPL‐positive, and 10 healthy female subjects with no history of neuropsychiatric abnormality. Results Analysis of fMRI data showed no differences in performance across groups on bilateral motor tasks. When analysis of variance was used, significant group differences were found in 2 executive function tasks (word generation and word rhyming) and in a working memory task (N‐Back). Patients positive for aPL demonstrated higher activation in bilateral frontal, temporal, and parietal cortices compared to controls during working memory and executive function tasks. SLE patients also demonstrated bilateral frontal and temporal activation during working memory and executive function tasks. Conclusion Compared to controls, both aPL‐positive and SLE patients had elevated cortical activation, primarily in the frontal lobes, during tasks involving working memory and executive function. These findings are consistent with cortical overactivation as a compensatory mechanism for early white matter neuropathology in these disorders.